Flexible perovskite solar cell based on dual-interface synergistic anchoring crosslinking of 4-mercaptobenzoic acid molecules and 6-mercaptohexyl-triphenylamine phosphate molecules

By using two small molecules, 4-MBA and 6-SCTP, a dual interface collaborative anchor crosslinking network is formed in a flexible perovskite solar cell, the problem of flexible perovskite solar cell prone to cracking under mechanical stress is solved, and mechanical stability and efficiency are significantly improved.

CN120035300APending Publication Date: 2025-05-23HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510461561.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2025-05-23

AI Technical Summary

Technical Problem

Flexible perovskite solar cells are prone to cracking under mechanical stress, resulting in deterioration of performance, and it is difficult for the prior art to take into account both interface adhesion and dynamic stress release.

Method used

By using two small molecules, 4-mercaptobenzoic acid (4-MBA) and 6-mercaptohexyl-triphenylphosphate (6-SCTP), an anchoring molecular layer and a crosslinking molecular layer are formed between the perovskite absorption layer and the hole transport layer, respectively, to build a dual interface collaborative anchoring crosslinking network.

Benefits of technology

The mechanical stability and efficiency of flexible perovskite solar cells are significantly improved, the unevenness and hole problems of perovskite films are improved, leakage current is avoided, and the time stability of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120035300A_ABST
    Figure CN120035300A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible perovskite solar cell based on dual interface synergistic anchoring crosslinking of a 4-mercaptobenzoic acid molecule and a 6-mercaptohexyl-triphenylamine phosphate ester molecule. Through molecular-level dynamic interface design, gradient chemical anchoring of the perovskite thin film and the electron transport layer is realized by using small molecules 4-MBA, and an anchoring-cross-linked network is constructed in combination with a polymer 6-SCTP containing mercaptan and phosphate functional groups, so that the mechanical stability of the flexible perovskite solar cell is remarkably improved, and the performance of the flexible perovskite solar cell is improved. And moreover, the efficiency and the time stability of the flexible perovskite solar cell are improved, and the flexible perovskite solar cell has a remarkable industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photovoltaic devices, and specifically relates to a flexible perovskite solar cell based on double interface synergistic anchoring and cross-linking of 4-mercaptobenzoic acid molecules and 6-mercaptohexyl-triphenylamine phosphate molecules. Background Art

[0002] Flexible perovskite solar cells have great potential in the field of wearable devices and flexible electronics due to their lightweight and bendable properties. However, problems such as weak interface bonding between the perovskite layer and the transport layer and easy cracking under mechanical stress have severely limited their application. The main reason for this is that when the perovskite film is repeatedly bent, there is considerable stress inside the film that cannot be released.

[0003] The residual stress of perovskite films mainly originates from thermal expansion mismatch and process conditions, which is a key factor leading to the performance degradation of f-PSCs. Poor interlayer contact will aggravate stress damage. At present, strategies such as introducing a buffer layer to alleviate lattice mismatch or adding organic molecules to release stress have been proven to effectively improve performance. For example, Wu et al. designed a crosslinker (4,5-(3-methyloxetane) dicarboxylic acid imidazole) containing C=O and C=N groups to regulate the spatial composition uniformity of perovskite films on flexible substrates and eliminate residual strain, which significantly improved the mechanical stability of f-PSCs and achieved a PCE of nearly 24% [ACS Energy Lett. 2023, 8, 3750]. Chen's team introduced the crosslinker borax into the perovskite film to form a stable coordination bond, so that the f-PSC maintained 91.8% of the initial PCE after 10,000 cycles at a bending radius of 5 mm [Adv. Mater. 2022,34, 2200320].

[0004] Existing technologies mostly use single molecule passivation or polymer toughening, but it is difficult to take into account both interface adhesion and dynamic stress release. Therefore, an innovative solution that synergistically enhances interface bonding and mechanical stability is urgently needed. The present invention uses small molecule 4-mercaptobenzoic acid (4-MBA) and organic molecule 6-mercaptohexyl-triphenylamine phosphate (6-SCTP) to construct an anchoring-crosslinking network through molecular-level dynamic interface design, which not only significantly improves the mechanical stability of f-PSCs, but also improves the efficiency and time stability of f-PSCs. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned existing technologies, the present invention provides a flexible perovskite solar cell based on the dual-interface synergistic anchoring and cross-linking of 4-mercaptobenzoic acid molecules and 6-mercaptohexyl-triphenylamine phosphate molecules. The present invention synergistically improves the mechanical durability and stability of flexible perovskite batteries through the chemical anchoring of one small molecule and the dynamic cross-linking of another small molecule. The preparation process of the present invention is a low-temperature process, which is of great significance for the development of flexible wearable photovoltaic products. The method of the present invention has the advantages of low-temperature preparation, low cost, and easy industrial production.

[0006] The flexible perovskite solar cell of the present invention based on the dual-interface synergistic anchoring and cross-linking of 4-mercaptobenzoic acid molecules and 6-mercaptohexyl-triphenylamine phosphate molecules is of the n-i-p type, and sequentially includes a flexible substrate, an electron transport layer, a perovskite absorption layer, a hole transport layer, and a metal back electrode from bottom to top.

[0007] The present invention provides a small molecule cross-linking layer between the hole transport layer and the perovskite absorption layer. By cross-linking the perovskite and the hole transport layer with cross-linking molecules, not only the stability of the flexible perovskite battery is improved, but also the problems of non-uniformity and holes in the perovskite film are solved, avoiding the leakage current caused by the direct contact between the perovskite layer and the conductive glass, and at the same time enhancing the electron extraction ability of the functional layer, thereby improving the battery efficiency.

[0008] Further, the cross-linking molecule is one of 6-mercaptohexyl-triphenylamine phosphate (6-SCTP), tetra-armed PEG-acrylate, or fluorinated acrylate.

[0009] The small molecule cross-linking layer is prepared by the following method:

[0010] Dissolve 5 mg - 15 mg of the cross-linking molecule in 1 ml of ethanol, stir and disperse evenly to obtain a mother liquor; take 50 μL of the mother liquor and spin-coat it on the perovskite absorption layer, and then cure it with ultraviolet light with an energy of 10 mW / cm 2 at 365 nm for 30 seconds to form a dynamic cross-linking layer. The spin-coating conditions are spin-coating at 3000 rpm for 30 s.

[0011] The present invention provides an anchoring molecule layer between the perovskite absorption layer and the electron transport layer, and anchors the perovskite absorption layer and the electron transport layer with anchoring molecules.

[0012] Further, the anchoring molecule is one of 4-mercaptobenzoic acid (4-MBA), lipoic acid, or 2-mercaptonicotinic acid.

[0013] The anchoring molecule layer is prepared by the following method:

[0014] Take 5-15 mg of anchoring molecules and dissolve them in 2 ml of ethanol, stir and disperse them evenly to form the mother solution; take 50 µL of the mother solution and spin-coat it on the electron transport layer, anneal at 100 °C for 5 minutes to form the anchoring molecule layer. The spin-coating condition is 3500 rpm for 20 s.

[0015] The flexible substrate is one of PET or PI.

[0016] The electron transport layer is selected from titanium oxide (TiO 2 ), tin oxide (SnO 2 )、ZnO、Vanadium oxide(V 2 O 5 )、ZnO 2 SnO 4 ) etc., but is not limited to the n-type semiconductor materials listed above.

[0017] The hole transport layer may be made of nickel oxide (NiO), molybdenum oxide (MoO 3 ), cuprous oxide (Cu 2 O), copper iodide (CuI), copper phthalocyanine (CuPc), cuprous thiocyanate (CuSCN), redox graphene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly-3,4-ethylenedioxythiophene: polystyrene sulfonate (PEDOT:PSS), 4-butyl-N,N-diphenylaniline homopolymer (PloyTPD), polyvinylcarbazole (PVK), etc., but not limited to the p-type semiconductor materials listed above.

[0018] The perovskite absorber layer is CH 3 NH 3 PbB 3 , CH 3 NH 3 PbI 3 , CH 3 NH 3 Pb (I 1-x Br x ) 3 Any one of , where 0≤x≤1.

[0019] Furthermore, the thickness of the electron transport layer is 10-20nm; the thickness of the anchoring molecule layer is 20-50nm; the thickness of the perovskite absorption layer is 300-800nm; the thickness of the small molecule cross-linking layer is 10-20nm; the thickness of the hole transport layer is 100-300nm; and the metal electrode is 60-200nm.

[0020] The present invention uses 4-MBA and 6-SCTP as anchoring molecules and cross-linking molecules to construct a flexible perovskite solar cell at low temperature on a flexible substrate. Different from the conventional single-layer small molecule to improve the stability of flexible batteries, this method anchors SnO through 4-MBA molecules under the perovskite film. 2 The thin film and perovskite film synergistically cross-link the perovskite and hole transport layer through 6-SCTP, which not only improves the stability of the flexible perovskite battery, but also improves the unevenness and porosity of the perovskite film, avoids the leakage current caused by direct contact between the perovskite layer and the conductive glass, and enhances the electron extraction ability of the functional layer, thereby improving the battery efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the perovskite solar cell structure of comparative example 1.

[0022] Figure 2 The perovskite solar cell structure with 4-MBA anchoring added to Example 1.

[0023] Figure 3 The perovskite solar cell structure with 6-SCTP cross-linking added to Example 2.

[0024] Figure 4 The structure of a perovskite solar cell with simultaneous addition of 4-MBA anchoring and 6-SCTP cross-linking.

[0025] Figure 5 Figure a is the molecular structure of 4-MBA, Figure b is the molecular structure of 2-mercaptonicotinic acid, and Figure c is the molecular structure of lipoic acid.

[0026] Figure 6 Figure a shows the molecular structure of 6-SCTP, Figure b shows the molecular structure of perfluorooctyl ethyl acrylate, and Figure c shows the molecular structure of PEGDA

[0027] Figure 7 SnO before and after spin coating of 4-MBA molecules 2 Film morphology. Figure 7 It can be seen that the 4-MBA molecules have evenly covered the SnO 2 .

[0028] Figure 8 The morphology of the perovskite film before and after bending 1000 times after spin coating 6-SCTP molecules. Figure 8 It can be seen that after anchoring-crosslinking, the mechanical stability of the perovskite film is significantly improved, and there are no obvious cracks before and after the film is bent.

[0029] Fig. 9 The current density and voltage diagram of perovskite solar cells with simultaneous addition of 4-MBA anchoring and 6-SCTP crosslinking. Fig. 9 It can be seen that the current density and corresponding open circuit voltage of the optimal device are obtained, verifying the efficiency of the device.

[0030] Fig.10 is the stability of the device over time after adding small molecules. Fig.10 It can be seen that the perovskite solar cells with both 4-MBA anchoring and 6-SCTP cross-linking have the best stability over time, and can maintain more than 90% of the original efficiency after 10,000 hours of stability.

[0031] Fig.11 The stability of the device after adding small molecules with the number of bending times. Fig.11 It can be seen that the perovskite solar cells with both 4-MBA anchoring and 6-SCTP cross-linking have the best mechanical stability and can maintain more than 90% of the original efficiency after 15,000 hours.

[0032] Fig.12 is the efficiency distribution of the device after adding small molecules. Fig.12 It can be seen that the efficiency of perovskite solar cells with the addition of 4-MBA anchoring and 6-SCTP cross-linking is also improved to a certain extent, reaching more than 24.5%.

[0033] Fig.13 The stability of perovskite solar cell devices prepared with different anchoring molecules with the number of bending times. Fig.13 It can be seen that the device with 4-MBA as the anchoring molecule has better mechanical stability.

[0034] Fig.14 The stability of perovskite solar cell devices prepared with different cross-linking molecules with the number of bending times. Fig.13 It can be seen that the device with 6-SCTP molecules as the cross-linking molecules has better mechanical stability. DETAILED DESCRIPTION

[0035] In order to make the technical scheme of the present invention better understood by the personnel in the field, the technical scheme in the specific implementation mode of the present invention will be clearly and completely described below in combination with the drawings in the implementation mode of the present invention. It is worth noting that the embodiments provided by the present invention are not limited to the best implementation mode, and do not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the enlightenment of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0036] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0037] The present invention has no particular limitation on the preparation process of the electron transport layer. For example, a solution spin coating method, a solution scraping method, a solution spraying method, a slit coating method or a hydrothermal growth method may be used.

[0038] The present invention has no particular limitation on the preparation process of the hole transport layer. For example, solution spin coating, solution scraping, slit coating or vapor phase method can be used. In some embodiments of the present application, the preparation method of the hole transport layer is slit coating.

[0039] The present invention has no particular limitation on the preparation process of the perovskite absorption layer. For example, solution spin coating, solution scraping, slit coating or steam coating may be used. In some embodiments of the present application, the preparation method of the perovskite absorption layer is solution spin coating.

[0040] The present invention has no particular limitation on the preparation process of the metal counter electrode, for example, a thermal evaporation method may be used.

[0041] In the present invention, the bendable diameter means that when the perovskite battery is folded in half, the inner side of the middle bending area is nearly arc-shaped, and the diameter corresponding to the arc on the outer side of the bending area is the bendable diameter.

[0042] The solar cell performance testing instrument of the present invention:

[0043] The current (I)-voltage (V) of the perovskite cell was measured using an IV curve test system (Guangyan Technology SS-X200R model). The solar simulator is equipped with a 300 W xenon light source, which has a light intensity of 100 mW / cm under AM1.5 standard sunlight. 2 The digital measuring meter used was Keithley 2400 model for signal acquisition; the effective area of ​​the battery was set to 40 mm × 40 mm, the scanning voltage range was 0 V-7 V, and the scanning rate was 0.2 V / s.

[0044] Based on the above tests, the current-voltage data, current density data and fill factor data of the perovskite battery are obtained. Based on the above data, the photoelectric conversion efficiency (PCE) and time (t) data are obtained, and the PCE-t curve of the perovskite battery is plotted.

[0045] Comparative Example 1:

[0046] This comparative example 1 adopts Figure 1 The structure shown is used to prepare a perovskite thin-film solar cell. The specific preparation process is as follows:

[0047] 1. Selection and processing of flexible substrates

[0048] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0049] 2. Preparation of electron transport layer

[0050] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0051] 3. Preparation of perovskite light-absorbing layer

[0052] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3, then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0053] 4. Preparation of hole transport layer

[0054] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0055] 5. Deposition of metal back electrode

[0056] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0057] Embodiment 1:

[0058] This embodiment 2 adopts Figure 2 The structure shown is used to prepare a perovskite thin film solar cell. The specific preparation process is as follows:

[0059] 1. Selection and processing of flexible substrates

[0060] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0061] 2. Preparation of electron transport layer

[0062] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0063] 3.4-MBA film preparation anchoring

[0064] Take 10 mg of 4-MBA and dissolve it in 2 ml of ethanol solution and stir for 2 h as the mother solution. Then take 50 µL and add it to the electron transport layer SnO 2 The film was spin-coated at 3500 rpm for 20 s and annealed at 100 °C for 5 min to form a monomolecular anchoring layer.

[0065] 4. Preparation of perovskite light-absorbing layer

[0066] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0067] 5. Preparation of hole transport layer

[0068] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0069] 6. Deposition of metal back electrode

[0070] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0071] Embodiment 2:

[0072] This embodiment 2 adopts Figure 3 The structure shown is used to prepare a perovskite thin film solar cell. The specific preparation process is as follows:

[0073] 1. Selection and processing of flexible substrates

[0074] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0075] 2. Preparation of electron transport layer

[0076] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0077] 3. Preparation of perovskite light-absorbing layer

[0078] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0079] 4. Preparation and cross-linking of 6-SCTP films

[0080] Take 10 mg of 6-SCTP and dissolve it in 1 ml of ethanol solution and stir for 1 hour as the mother solution. Then take 50 µL and spin-coat it on the device with spin-coated perovskite film at 3000 rpm for 30 s. Then cure it with 365 nm UV light with energy of 10 mW / cm² for 30 seconds to form a dynamic cross-linking layer.

[0081] 5. Preparation of hole transport layer

[0082] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0083] 6. Deposition of metal back electrode

[0084] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0085] Embodiment 3:

[0086] This embodiment 3 adopts Figure 4 The structure shown is used to prepare a perovskite thin film solar cell. The specific preparation process is as follows:

[0087] 1. Selection and processing of flexible substrates

[0088] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0089] 2. Preparation of electron transport layer

[0090] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0091] 3.4-MBA film preparation anchoring

[0092] Take 10 mg of 4-MBA and dissolve it in 2 ml of ethanol solution and stir for 2 h as the mother solution. Then take 50 µL and add it to the electron transport layer SnO 2 The film was spin-coated at 3500 rpm for 20 s and annealed at 100 °C for 5 min to form a monomolecular anchoring layer.

[0093] 4. Preparation of perovskite light-absorbing layer

[0094] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0095] 5.6-SCTP film preparation and cross-linking

[0096] Take 10 mg of 6-SCTP and dissolve it in 1 ml of ethanol solution and stir for 1 hour as the mother solution. Then take 50 µL and spin-coat it on the device with spin-coated perovskite film at 3000 rpm for 30 s. Then cure it with 365 nm UV light with energy of 10 mW / cm² for 30 seconds to form a dynamic cross-linking layer.

[0097] 6. Preparation of hole transport layer

[0098] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0099] 7. Deposition of metal back electrode

[0100] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0101] Embodiment 4:

[0102] This embodiment 4 adopts Figure 3 The structure shown is used to prepare a perovskite thin-film solar cell. The specific preparation process is as follows:

[0103] 1. Selection and processing of flexible substrates

[0104] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0105] 2. Preparation of electron transport layer

[0106] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0107] 3.4-MBA film preparation anchoring

[0108] Take 5 mg of 4-MBA and dissolve it in 2 ml of ethanol solution and stir for 2 h as the mother solution. Then take 50 µL and add it to the electron transport layer SnO 2 The film was spin-coated at 3500 rpm for 20 s and annealed at 100 °C for 5 min to form a monomolecular anchoring layer.

[0109] 4. Preparation of perovskite light-absorbing layer

[0110] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0111] 5.6-SCTP film preparation and cross-linking

[0112] Take 10 mg of 6-SCTP and dissolve it in 1 ml of ethanol solution and stir for 1 hour as the mother solution. Then take 50 µL and spin-coat it on the device with spin-coated perovskite film at 3000 rpm for 30 s. Then cure it with 365 nm UV light with energy of 10 mW / cm² for 30 seconds to form a dynamic cross-linking layer.

[0113] 6. Preparation of hole transport layer

[0114] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0115] 7. Deposition of metal back electrode

[0116] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0117] Embodiment 5:

[0118] This embodiment 5 adopts Figure 3 The structure shown is used to prepare a perovskite thin-film solar cell. The specific preparation process is as follows:

[0119] 1. Selection and processing of flexible substrates

[0120] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0121] 2. Preparation of electron transport layer

[0122] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0123] 3.4-MBA film preparation anchoring

[0124] Take 15 mg of 4-MBA and dissolve it in 2 ml of ethanol solution and stir for 2 h as the mother solution. Then take 50 µL and add it to the electron transport layer SnO 2 The film was spin-coated at 3500 rpm for 20 s and annealed at 100 °C for 5 min to form a monomolecular anchoring layer.

[0125] 4. Preparation of perovskite light-absorbing layer

[0126] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 )0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0127] 5.6-SCTP film preparation and cross-linking

[0128] Take 10 mg of 6-SCTP and dissolve it in 1 ml of ethanol solution and stir for 1 h as the mother solution. Then take 50 µL and spin-coat it on the device with spin-coated perovskite film at 3000 rpm for 30 s. Then use 365 nm energy of 10 mW / cm 2 UV light was used to cure the film for 30 seconds to form a dynamic cross-linking layer.

[0129] 6. Preparation of hole transport layer

[0130] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0131] 7. Deposition of metal back electrode

[0132] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0133] Embodiment 6:

[0134] This embodiment 6 adopts Figure 3 The structure shown is used to prepare a perovskite thin film solar cell. The specific preparation process is as follows:

[0135] 1. Selection and processing of flexible substrates

[0136] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0137] 2. Preparation of electron transport layer

[0138] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0139] 3.4-MBA film preparation anchoring

[0140] Take 10 mg of 4-MBA and dissolve it in 2 ml of ethanol solution and stir for 2 h as the mother solution. Then take 50 µL and add it to the electron transport layer SnO 2 The film was spin-coated at 3500 rpm for 20 s and annealed at 100 °C for 5 min to form a monomolecular anchoring layer.

[0141] 4. Preparation of perovskite light-absorbing layer

[0142] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0143] 5.6-SCTP film preparation and cross-linking

[0144] Take 5 mg of 6-SCTP and dissolve it in 1 ml of ethanol solution and stir for 1 h as the mother solution. Then take 50 µL and spin-coat it on the device with spin-coated perovskite film at 3000 rpm for 30 s. Then use 365 nm energy of 10 mW / cm 2 UV light was used to cure the film for 30 seconds to form a dynamic cross-linking layer.

[0145] 6. Preparation of hole transport layer

[0146] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0147] 7. Deposition of metal back electrode

[0148] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0149] Embodiment 7:

[0150] This embodiment 7 adopts Figure 3 The structure shown is used to prepare a perovskite thin-film solar cell. The specific preparation process is as follows:

[0151] 1. Selection and processing of flexible substrates

[0152] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0153] 2. Preparation of electron transport layer

[0154] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0155] 3.4-MBA film preparation anchoring

[0156] Take 10 mg of 4-MBA and dissolve it in 2 ml of ethanol solution and stir for 2 h as the mother solution. Then take 50 µL and add it to the electron transport layer SnO 2 The film was spin-coated at 3500 rpm for 20 s and annealed at 100 °C for 5 min to form a monomolecular anchoring layer.

[0157] 4. Preparation of perovskite light-absorbing layer

[0158] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0159] 5.6-SCTP film preparation and cross-linking

[0160] Take 15 mg of 6-SCTP and dissolve it in 1 ml of ethanol solution and stir for 1 h as the mother solution. Then take 50 µL and spin-coat it on the device with spin-coated perovskite film at 3000 rpm for 30 s. Then use 365 nm energy of 10 mW / cm 2 UV light was used to cure the film for 30 seconds to form a dynamic cross-linking layer.

[0161] 6. Preparation of hole transport layer

[0162] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0163] 7. Deposition of metal back electrode

[0164] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0165] Embodiment 8:

[0166] This embodiment 8 adopts Figure 3 The structure shown is used to prepare a perovskite thin-film solar cell. The specific preparation process is as follows:

[0167] 1. Selection and processing of flexible substrates

[0168] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0169] 2. Preparation of electron transport layer

[0170] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0171] 3.4-MBA film preparation anchoring

[0172] Take 5 mg of 4-MBA and dissolve it in 2 ml of ethanol solution and stir for 2 h as the mother solution. Then take 50 µL and add it to the electron transport layer SnO 2 The film was spin-coated at 3500 rpm for 20 s and annealed at 100 °C for 5 min to form a monomolecular anchoring layer.

[0173] 4. Preparation of perovskite light-absorbing layer

[0174] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0175] 5.6-SCTP film preparation and cross-linking

[0176] Take 5 mg of 6-SCTP and dissolve it in 1 ml of ethanol solution and stir for 1 h as the mother solution. Then take 50 µL and spin-coat it on the device with spin-coated perovskite film at 3000 rpm for 30 s. Then use 365 nm energy of 10 mW / cm 2UV light was used to cure the film for 30 seconds to form a dynamic cross-linking layer.

[0177] 6. Preparation of hole transport layer

[0178] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0179] 7. Deposition of metal back electrode

[0180] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0181] Embodiment 9:

[0182] This embodiment 9 adopts Figure 3 The structure shown is used to prepare a perovskite thin film solar cell. The specific preparation process is as follows:

[0183] 1. Selection and processing of flexible substrates

[0184] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0185] 2. Preparation of electron transport layer

[0186] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0187] 3.4-MBA film preparation anchoring

[0188] Take 15 mg of 4-MBA and dissolve it in 2 ml of ethanol solution and stir for 2 h as the mother solution. Then take 50 µL and add it to the electron transport layer SnO 2 The film was spin-coated at 3500 rpm for 20 s and annealed at 100 °C for 5 min to form a monomolecular anchoring layer.

[0189] 4. Preparation of perovskite light-absorbing layer

[0190] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0191] 5.6-SCTP film preparation and cross-linking

[0192] Take 15 mg of 6-SCTP and dissolve it in 1 ml of ethanol solution and stir for 1 h as the mother solution. Then take 50 µL and spin-coat it on the device with spin-coated perovskite film at 3000 rpm for 30 s. Then use 365 nm energy of 10 mW / cm 2 UV light was used to cure the film for 30 seconds to form a dynamic cross-linking layer.

[0193] 6. Preparation of hole transport layer

[0194] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0195] 7. Deposition of metal back electrode

[0196] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 -6 Torr) to ensure the purity and uniformity of the metal layer.

[0197] Embodiment 10:

[0198] This embodiment 10 adopts Figure 2 The structure shown in the figure is used to prepare a perovskite thin film solar cell, where only the 4-MBA film is replaced by a 2-mercaptonicotinic acid film. The specific preparation process is as follows:

[0199] 1. Selection and processing of flexible substrates

[0200] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0201] 2. Preparation of electron transport layer

[0202] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0203] 3. Preparation and anchoring of 2-mercaptonicotinic acid film

[0204] Take 3 mg of 2-mercaptonicotinic acid and dissolve it in 2 ml of a 1:1 methanol / ethanol mixed solvent and stir for 2 h as the mother solution. Then take 50 µL and add it to the electron transport layer SnO 2 The film was spin coated at 4000 rpm for 20 s and annealed at 90 °C for 3 min.

[0205] 4. Preparation of perovskite light-absorbing layer

[0206] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0207] 5. Preparation of hole transport layer

[0208] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0209] 6. Deposition of metal back electrode

[0210] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0211] Embodiment 11:

[0212] This embodiment 11 adopts Figure 2 The structure shown in the figure is used to prepare a perovskite thin film solar cell, where only the 4-MBA film is replaced by a lipoic acid film. The specific preparation process is as follows:

[0213] 1. Selection and processing of flexible substrates

[0214] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0215] 2. Preparation of electron transport layer

[0216] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0217] 3. Preparation and anchoring of lipoic acid film

[0218] Take 8 mg of 2-mercaptonicotinic acid and dissolve it in 2 ml of chloroform solvent. Add 0.5% of antioxidant BHT (butylated hydroxytoluene) and stir for 1 hour as the mother solution. Then take 50 μL of it and add it to the electron transport layer SnO 2The film was spin coated at 2000 rpm for 40 s and annealed at 80 °C for 10 min.

[0219] 4. Preparation of perovskite light-absorbing layer

[0220] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0221] 5. Preparation of hole transport layer

[0222] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0223] 6. Deposition of metal back electrode

[0224] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0225] Embodiment 12:

[0226] This embodiment 12 adopts Figure 3To fabricate a perovskite thin-film solar cell with the structure shown, only replace the 6-SCTP thin film with a perfluorooctylethyl acrylate thin film. The specific fabrication process is as follows:

[0227] 1. Selection and treatment of the flexible substrate

[0228] Select polyethylene terephthalate (PET) with a thickness of 100 microns as the flexible substrate. In a clean environment, use an ultraviolet ozone cleaner to perform surface treatment on the PET substrate to improve its hydrophilicity and adhesion.

[0229] 2. Preparation of the electron transport layer

[0230] Prepare a layer of SnO 2 as the electron transport layer using chemical bath deposition (CBD). First, it is necessary to prepare a mother liquor of SnCl 2 ·2H 2 O. Dissolve 4.2 g of urea in 400 mL of deionized water, then add 100 µL of mercaptoacetic acid and 4 mL of HCl (37 wt%). After thoroughly shaking and mixing the solution, place it in the refrigerator and let it stand for three days. Then, take 200 µL of the well-stood SnCl 2 ·2H 2 O mother liquor and mix it with 100 mL of deionized water to prepare a 0.02 M dilution. Then, immerse the treated ITO substrate in the prepared dilution and place it in an oven at 90 °C for 1 h. After sufficient reaction, rinse it repeatedly with deionized water until the rinse water is clear and transparent, and dry it with an air gun. Finally, anneal it on a heating stage at 150 °C for 1 h to finally obtain the electron transport layer.

[0231] 3. Preparation of the perovskite light-absorbing layer

[0232] Dissolve 460 mg of PbI 2 , 23 mg of CsI, 181 mg of CH 3 NH 3 I, and 20 mg of MACl in a DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 . Then, take 50 µL of the solution and spin it at 3500 rpm for 60 s. Then, anneal it at 100 °C for 1 min first and then at 150 °C for 10 min to obtain a perovskite thin film with a thickness of approximately 600 nm.

[0233] 4. Preparation of crosslinked perfluorooctylethyl acrylate thin film

[0234] 5 wt% perfluorooctyl ethyl acrylate was dissolved in 2 ml perfluorohexane and ultrasonically shaken for 1 h as the mother solution. Then 50 µL was taken and dynamically rotated at 2500 rpm for 30 s on the device with spin-coated perovskite film, and annealed at 120 °C for 10 minutes to form a dynamic cross-linking layer.

[0235] 5. Preparation of hole transport layer

[0236] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0237] 6. Deposition of metal back electrode

[0238] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0239] Embodiment 13:

[0240] This embodiment 13 adopts Figure 3 The structure shown in the figure is used to prepare a perovskite thin film solar cell, where only the 6-SCTP film is replaced by a PEGDA film. The specific preparation process is as follows:

[0241] 1. Selection and processing of flexible substrates

[0242] Polyethylene terephthalate (PET) with a thickness of 100 μm was selected as the flexible substrate. In a clean environment, the PET substrate was surface treated using a UV-ozone cleaning machine to improve its hydrophilicity and adhesion.

[0243] 2. Preparation of electron transport layer

[0244] A layer of SnO was prepared by chemical bath deposition (CBD). 2 As an electron transport layer. First, SnCl 2 ·2H 2 O mother liquor. Dissolve 4.2 g urea in 400 mL deionized water, then add 100 µL thioglycolic acid and 4 mL HCl (37 wt%), shake the solution thoroughly and place it in a refrigerator for three days. Then, take 200 µL of the SnCl 2 ·2H 2 The O mother liquor was mixed with 100 mL of deionized water to form a 0.02 M dilution solution. The treated ITO substrate was then immersed in the prepared dilution solution and placed in a 90°C oven for 1 h. After sufficient reaction, it was rinsed repeatedly with deionized water until the rinse solution was clear and transparent, and then dried with an air gun. Finally, it was annealed on a 150°C heating table for 1 h to obtain the electron transport layer.

[0245] 3. Preparation of perovskite light-absorbing layer

[0246] 460 mg PbI 2 、23 mg CsI、181 mg CH 3 NH 3 I. Dissolve 20 mg MACl in DMF:DMSO = 4:1 solution to prepare (CH 3 NH 3 ) 0.9 Cs 0.1 PbI 3 , then 50 µL of the solution was taken and rotated at 3500 rpm for 60 s, and then annealed at 100°C for 1 min and then at 150°C for 10 min to obtain a perovskite film with a thickness of approximately 600 nm.

[0247] 4. Preparation and cross-linking of PEGDA films

[0248] Take 5 wt% PEGDA dissolved in 2 ml ethanol and shake for 1 hour as the mother solution, then take 50 µL and dynamically spin it at 2000 rpm for 15 s on the device with spin-coated perovskite film, irradiate it with 365 nm ultraviolet light (10 mW / cm²) for 30 seconds, and then anneal it at 80°C for 1 minute to form a dynamic cross-linking layer.

[0249] 5. Preparation of hole transport layer

[0250] Before preparing the hole transport layer solution, it is necessary to prepare the mother liquor of lithium salt and FK209. The mother liquor of lithium salt is prepared by adding 520 mg of lithium bis(trifluoromethanesulfonyl)imide powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h until dissolved to obtain the lithium salt solution; the mother liquor of FK209 is prepared by adding 450 mg of FK209 powder to 1 mL of acetonitrile (ACN) and stirring at room temperature for 2 h on a magnetic stirrer until dissolved to obtain the FK209 solution. Weigh 72 mg of Spiro-OMeTAD, 14.5 µL of FK209 solution, 14 µL of lithium salt, 23.6 µL of TBP solution, and 1 mL of chlorobenzene into a 3 mL glass bottle to prepare the Spiro-OMeTAD hole transport layer solution, and then take 50 µL of the solution and rotate at 4500 rpm for 30 s to dynamically spin-coat the solution on the perovskite film to prepare the hole transport layer.

[0251] 6. Deposition of metal back electrode

[0252] A layer of gold (Ag) was deposited on the hole transport layer by thermal evaporation as the metal back electrode. The evaporation rate was controlled at 0.1 nm / s until the desired thickness (about 100 nm) was reached. During the entire evaporation process, a high vacuum environment (<1×10 - 6 Torr) to ensure the purity and uniformity of the metal layer.

[0253]

[0254] It can be seen from Comparative Example 1 and Example 1 that after adding 4-MBA anchoring molecules, the mechanical stability of the flexible perovskite battery is improved to a certain extent.

[0255] It can be seen from Comparative Example 1 and Example 2 that after adding 6-SCTP cross-linking molecules, the mechanical stability of the flexible perovskite battery is improved to a certain extent.

[0256] It can be seen from Comparative Example 1, Example 1, Example 2 and Example 3 that after adding 4-MBA anchoring molecules and 6-SCTP cross-linking molecules at the same time, the mechanical stability of the flexible perovskite battery is significantly improved.

[0257] It can be seen from Examples 2-5 that in the device with both 4-MBA anchor molecules and 6-SCTP cross-linking molecules added, when the 6-SCTP cross-linking molecule spin coating concentration is 10 mg / ml, the 4-MBA anchor molecules at a spin coating concentration of 5 mg / ml have better mechanical stability.

[0258] It can be seen from Examples 3-9 that in the device with both 4-MBA anchor molecules and 6-SCTP crosslinking molecules added, the best mechanical stability is achieved when the spin coating concentration of 6-SCTP crosslinking molecules is 10 mg / ml and the spin coating concentration of 4-MBA anchor molecules is 5 mg / ml.

Claims

1. A flexible perovskite solar cell based on dual interface synergistic anchoring and cross-linking of 4-mercaptobenzoic acid molecules and 6-mercaptohexyl-triphenylamine phosphate molecules, characterized in that: The flexible perovskite solar cell is of NIP type, and includes, from bottom to top, a flexible substrate, an electron transport layer, a perovskite absorption layer, a hole transport layer, and a metal back electrode; A small molecule cross-linking layer is provided between the hole transport layer and the perovskite absorption layer, and the perovskite and the hole transport layer are cross-linked by cross-linking molecules; An anchoring molecule layer is provided between the perovskite absorption layer and the electron transport layer, and the perovskite absorption layer and the electron transport layer are anchored by the anchoring molecules.

2. The flexible perovskite solar cell according to claim 1, characterized in that: The cross-linking molecule is one of 6-mercaptohexyl-triphenylamine phosphate, four-arm PEG-acrylate or fluorine-containing acrylate.

3. The flexible perovskite solar cell according to claim 2, characterized in that: The small molecule cross-linking layer is prepared by the following method: Take 5mg-15mg of the cross-linked molecules and dissolve them in 1ml of ethanol. Stir and disperse them evenly to form the mother solution. Take 50µL of the mother solution and spin-coat it on the perovskite absorption layer. Then spin-coat it at 365nm with an energy of 10 mW / cm 2 The film was cured under UV light for 30 seconds to form a dynamic cross-linking layer.

4. The flexible perovskite solar cell according to claim 3, characterized in that: The spin coating condition was 3000 rpm for 30 s.

5. The flexible perovskite solar cell according to claim 1, characterized in that: The anchoring molecule is one of 4-mercaptobenzoic acid, lipoic acid or 2-mercaptonicotinic acid.

6. The flexible perovskite solar cell according to claim 5, characterized in that: The anchoring molecule layer is prepared by the following method: Take 5-15 mg of anchoring molecules and dissolve them in 2 ml of ethanol, stir and disperse them evenly to form the mother solution; take 50 µL of the mother solution and spin-coat it on the electron transport layer, anneal at 100 ° C for 5 minutes to form an anchoring molecule layer.

7. The flexible perovskite solar cell according to claim 6, characterized in that: The spin coating condition was 3500 rpm for 20 s.

8. The flexible perovskite solar cell according to claim 1, characterized in that: The electron transport layer is made of one or more n-type semiconductor materials selected from titanium oxide, tin oxide, zinc oxide, vanadium oxide, and zinc tin oxide; The hole transport layer can be prepared from one or more p-type semiconductor materials selected from nickel oxide, molybdenum oxide, cuprous oxide, copper iodide, copper phthalocyanine, cuprous thiocyanate, redox graphene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly-3,4-ethylenedioxythiophene: polystyrene sulfonate, 4-butyl-N,N-diphenylaniline homopolymer, and polyvinylcarbazole.

9. The flexible perovskite solar cell according to claim 1, characterized in that: The perovskite absorption layer is CH3NH3PbBr3, CH3NH3PbI3, CH3NH3Pb (I 1-x Br x )3, where 0≤x≤1.

10. The flexible perovskite solar cell according to any one of claims 1 to 9, characterized in that: The thickness of the electron transport layer is 10-20nm; the thickness of the anchoring molecule layer is 20-50nm; the thickness of the perovskite absorption layer is 300-800nm; the thickness of the small molecule cross-linking layer is 10-20nm; the thickness of the hole transport layer is 100-300nm; and the thickness of the metal electrode is 60-200nm.